Rhesus macaque θ-defensin RTD-1 inhibits proinflammatory cytokine secretion and gene expression by inhibiting the activation of NF-κB and MAPK pathways. Issue 6 (12th August 2015) - Tongaonkar, Prasad; Trinh, Katie K; Schaal, Justin B; Tran, Dat; Gulko, Percio S; Ouellette, André J; Selsted, Michael E
Abstract : The anti-inflammatory effects of θ-defensin RTD-1 are mediated by cell signaling pathways that down-regulate expression of pro-inflammatory cytokines. Abstract: θ-Defensins are pleiotropic, macrocyclic peptides that are expressed uniquely in Old World monkeys. The peptides are potent, broad-spectrum microbicides that also modulate inflammatory responses in vitro and in animal models of viral infection and polymicrobial sepsis. θ-Defensins suppress proinflammatory cytokine secretion by leukocytes stimulated with diverse Toll-like receptor (TLR) ligands. Studies were performed to delineate anti-inflammatory mechanisms of rhesus θ-defensin 1 (RTD-1), the most abundant θ-defensin isoform in macaque granulocytes. RTD-1 reduced the secretion of tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-8 in lipopolysaccharide (LPS)-stimulated human blood monocytes and THP-1 macrophages, and this was accompanied by inhibition of nuclear factor κB (NF-κB) activation and mitogen-activated protein kinase (MAPK) pathways. Peptide inhibition of NF-κB activation occurred following stimulation of extracellular (TLRs 1/2 and 4) and intracellular (TLR9) receptors. Although RTD-1 did not inhibit MAPK in unstimulated cells, it induced phosphorylation of Akt in otherwise untreated monocytes and THP-1 cells. In the latter, this occurred within 10 min of RTD-1 treatment and produced a sustained elevation of phosphorylated Akt (pAkt) for at least 4 h. pAkt is a negative regulator of MAPK and NF-κB activation. RTD-1 inhibited IκBα degradation and p38 MAPK phosphorylation, and stimulated Akt phosphorylation in LPS-treated human primary monocytes and THP-1 macrophages. Specific inhibition of phosphatidylinositol 3-kinase (PI3K) blocked RTD-1-stimulated Akt phosphorylation and reversed the suppression of NF-κB activation by the peptide. These studies indicate that the anti-inflammatory properties of θ-defensins are mediated by activation of the PI3K/Akt pathway and suppression of proinflammatory signals in immune-stimulated cells.